Management of pancreatic trauma: a single center experience - Mathiyalagan, Ashokkumar; Subbarayan, Shankar; Rosemary, Livin Jose Joseph; Kalyanashanmugam, Sivakumar; Raju, Prabhakaran; Chidambaranathan, Sugumar; Lakshmanamoorthy, Naganath Babu Obla (International Surgery Journal, 2022)
Background: Traumatic injury to the pancreas is rare and frequently overlooked. High index of suspicion is required in diagnosing pancreatic injury and management is challenging even with experienced trauma surgeons. The aim of this study was to report our experience in the management of pancreatic injuries. Methods: We analyzed 39 patients with pancreatic injury managed in our center from January 2016- December 2021. Data regarding patients’ demographics, mode of injury, American association for the surgery of trauma-organ injury scale (AAST-OIS) grade of pancreatic injury, associated injuries, management, morbidity and mortality were collected for analysis. Results: The study included 39 patients who presented with blunt injury abdomen (AAST-OIS grading: grade 2 (n=6), grade 3 (n=29), grade 4 (n=4)) with mean age 28.9 years. Associated injuries were present in 41% of patients (n=16). Thirteen patients had non-operative management-5 of them were managed conservatively without any intervention; 8 of them had non-surgical intervention in the form of Percutaneous Drainage or Endoscopic Retrograde Cholangio Pancreatography with Pancreatic duct stent for peri-pancreatic collection or ductal injury. But the rate of readmission for recurrent pancreatitis and reintervention for peri-pancreatic collection was 46% and 38% respectively in these patients. Twenty-six patients underwent surgery-distal pancreato splenectomy, laparotomy and external drainage, Roux-en Y pancreaticojejunostomy. Conclusions: Management of high-grade pancreatic injuries needs technical expertise. Early diagnosis and appropriate surgical management in high-grade pancreatic injuries carries favorable outcomes. Delayed presentation with sepsis is associated with high mortality.